Politeness Strategies in Locker Room Communication: A Pragmatic Analysis of Bojan Hodak's Utterances in Persib Bandung - Muhammad Ferdiansyah Nugraha; Ruminda Ruminda; Erfan Muhammad Fauzi (Journal of English Language and Education, 2026)
This study examines the politeness strategies employed by Bojan Hodak in locker room communication and analyzes how these strategies contribute to maintaining team cohesion in Persib Bandung during the 2024/2025 BRI Liga 1 season. Using a qualitative descriptive method, data were collected from 34 locker room videos on Persib Bandung's official YouTube channel, yielding 68 utterances. Eight utterances were selected through purposive sampling based on their clarity in representing the four politeness strategy types proposed by Brown and Levinson (1987). The findings reveal that Bojan Hodak employs positive politeness, negative politeness, bald on record, and off record strategies to deliver motivation, instructions, and evaluations. These strategies function as pragmatic tools that balance authority, solidarity, and interpersonal respect, thereby maintaining team cohesion